Sustainable value: the perspective of horticultural producers in Arctic Norway - Halland, Hilde; Bertella, Giovanna; Kvalvik, Ingrid (International Food and Agribusiness Management Review, 2020)
Aiming for sustainable development of food value chains several assessment methods are developed, however it seems challenging to go from assessment to actual change. A solution proposed is increased stakeholder involvement also in the assessment phase. The perspective on sustainability varies depending on several variables, among which the geographical context where the producers are located. The perspective of the latter is of paramount importance as these are the actors on who, ultimately, possible changes towards sustainability depend. In this article, we applied a qualitative approach to investigate the farmers’ perspective on sustainability, in the horticultural production in Arctic Norway. We found that many of the premises for sustainable food production are present. The main challenges are lack of long-term planning, dependency of rented land as well as fluctuating yield and income. Producer’s network is essential for development as well as introduction of technical improvements. The study shows the importance of contextualisation of sustainability, as well as pointing at concerns about trade-offs between sustainability dimensions and themes in the proposed model. The research contributes to method development by demonstrating how a qualitative approach is a fruitful method to unravel the complexities of sustainability in food production.